1989
DOI: 10.1021/la00086a016
|View full text |Cite
|
Sign up to set email alerts
|

Electrified droplet fission and the Rayleigh limit

Abstract: The measured isoelectric points of the bubbles were consistently very close to the isoelectric points of the free amine or free acid precipitate, which appear in alkaline solutions for amine and in acid solutions for fatty acids.This indicates the electric charge of bubbles in such systems results from the armoring of bubbles by the partially hydrophobic surfactant precipitate.Registry No. Dodecylamine hydrochloride, 929-73-7; lauric acid, 143-07-7; sodium oleate, 143-19-1; sodium dodecyl sulfate, 151-21-3; so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
179
4
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(195 citation statements)
references
References 10 publications
11
179
4
1
Order By: Relevance
“…The increase in OH -concentration is related to the decrease in the droplet volume, attributable to evaporation along the spray plume. The evaporation rate follows the surface evaporation limit law, which leads to a simple dependence of the droplet radius on time t [55,56] (R=R 0 -9.96 10 -5 t, for water droplets at 300 K). Assuming an initial droplet diameter of 3 μm [38], and a droplet velocity of~1 m/s [54], evaporation of droplets leads to~27-fold decrease in the volume at 20 mm.…”
Section: Profiling the Plume Phmentioning
confidence: 99%
“…The increase in OH -concentration is related to the decrease in the droplet volume, attributable to evaporation along the spray plume. The evaporation rate follows the surface evaporation limit law, which leads to a simple dependence of the droplet radius on time t [55,56] (R=R 0 -9.96 10 -5 t, for water droplets at 300 K). Assuming an initial droplet diameter of 3 μm [38], and a droplet velocity of~1 m/s [54], evaporation of droplets leads to~27-fold decrease in the volume at 20 mm.…”
Section: Profiling the Plume Phmentioning
confidence: 99%
“…This capability allowed simultaneous levitation with subsequent separation of a population of droplets created from a single starting solution, but the droplets had varied magnitudes of net charge. After the droplets were ejected from the EDB and collected on a glass slide or MALDI plate, the solids contained in the deposited droplets were characterized using microscopy and MALDI-TOF-MS. T he physics of droplets that possess net charge is a subject that continues to receive considerable theoretical and experimental attention 140 years after initial independent studies by Lord Kelvin and Lord Rayleigh [1][2][3][4][5][6][7]. Less well characterized is the condensed phase chemistry that could occur within such droplets as a result of the net charge that is localized in the diffuse layer at the droplet-air interface [8,9].…”
mentioning
confidence: 99%
“…However, Figure 1b also revealed that not all the sample material was deposited in this spot, with some of the material spreading as far as 750 m away. The spreading of material observed was due to the evaporating droplets becoming electrostatically unstable during transit through the EDB, causing them to undergo Coulomb fission [22]. In support of these visual observations, the S/N of the lysozyme molecule with a single proton adducted in the mass spectra collected from this spot, denoted by the arrow in Figure 1b, was poor ( Figure 2a).…”
Section: The Role Of a Surface Tension Modifier On Sample Spot Preparmentioning
confidence: 65%
“…The amount of net excess charge a droplet can carry is directly proportional to the square root of its surface tension [22], so an increase in the surface tension will reduce the tendency for a droplet to undergo fission. A new solution was made that contained 0.8% glycerol by volume (Solution Ib, Table 1).…”
Section: The Role Of a Surface Tension Modifier On Sample Spot Preparmentioning
confidence: 99%